CD10 expression in gastric adenocarcinoma and its correlation with histopathological features and lymph node metastasis - Mohan, Bhavya Pappalamukalel; Krishnan, Sharath Kesavan (Asian Journal of Medical Sciences, 2021)
Background: Gastric cancer is one of the most common cancers worldwide. Invasion and metastasis are known prognostic factors. Previous studies have suggested CD10 expression in the epithelium and stroma of various carcinomas is associated with more aggressive behavior of the tumor. Aims and Objective: To study the immunohistochemical expression of CD10 in stromal cells of gastric adenocarcinoma and to correlate the expression with various clinicopathological features and lymph node metastasis. Materials and Methods: A cross sectional study of CD10 expression in 40 cases of gastric carcinoma in gastrectomy specimens was done. CD10 expression was correlated with age, gender, tumor site, tumor grade, histologic sub type, depth of invasion and lymph node status. Results: Out of 40 cases, 72.5% were males and 27.5% were females. Majority of cases were seen in 6th and 7th decades. Antrum was the most common location (70%) and intestinal morphology was the commonest histologic subtype (47.5%). Tumor size ranged from 2.5 to 11cms. 40% tumors were well differentiated. Majority (62.5%) of the tumors were in T3 stage. 25 (62.5%) cases showed a positive CD10 expression in stromal cells. Stromal CD10 expression in gastric carcinoma did not correlate with the age and gender of the cases as well as the location and size of the tumor, histologic subtype and lymph node involvement but correlated with depth of invasion (T stage) (p <0.05). Conclusion: CD10 expression in gastric adenocarcinoma shows a significant correlation with depth of invasion. CD10 may be used as an immunohistochemical surrogate of tumor behavior.